Vapor intrusion models for petroleum and chlorinated volatile organic compounds; opportunities for future improvements - Bekele, Dawit N; Naidu, Ravi; Bowman, Mark; Chadalavada, Sreenivasulu (Vadose zone journal, 2013)
The natural attenuation (NA) of volatile organic compounds (VOCs) is becoming recognized as a means of remediating contaminated sites and is generating widespread research interest. Recently, researchers incorporated NA into a vapor intrusion model (VIM) to more precisely predict the potential risk to humans and to more effectively screen contaminated sites. The NA of VOCs is a complex phenomenon that includes a range of biogeochemical reactions and physical processes. In this review, the various processes are discussed, including factors contributing to natural attenuation of VOCs in the unsaturated subsurface and their implications for site screening and risk assessment by a VIM. Vapor intrusion is the subject of active research focusing on a complex transport medium (subsurface soils) for which reliable and accurate mathematical models are required. The application of mathematical algorithms to simulate these complex processes often requires simplification and certain assumptions. Consequently, the simplifications and assumptions influence the model's predictive output. An overview of the theoretical basis and model algorithms of recently published models that account for the NA of volatile petroleum hydrocarbons in subsurface soils is provided. We also highlight the need to include the NA of chlorinated hydrocarbons in the VIM.